Evaluation of Industrially Applied Heat‐Transfer Fluids as Liquid Organic Hydrogen Carrier Systems. Issue 1 (16th August 2013) - Brückner, Nicole; Obesser, Katharina; Bösmann, Andreas; Teichmann, Daniel; Arlt, Wolfgang; Dungs, Jennifer; Wasserscheid, Peter
Abstract Liquid organic hydrogen carrier (LOHC) systems offer a very attractive method for the decentralized storage of renewable excess energy. In this contribution, industrially well‐established heat‐transfer oils (typically sold under trade names, e.g., Marlotherm) are proposed as a new class of LOHC systems. It is demonstrated that the liquid mixture of isomeric dibenzyltoluenes (m.p. −39 to −34 °C, b.p. 390 °C) can be readily hydrogenated to the corresponding mixture of perhydrogenated analogues by binding 6.2 wt % of H2. The liquid H2‐rich form can be stored and transported similarly to diesel fuel. It readily undergoes catalytic dehydrogenation at temperatures above 260 °C, which proves its applicability as a reversible H2 carrier. The presented LOHC systems are further characterized by their excellent technical availability at comparably low prices, full registration of the H2‐lean forms, and excellent thermal stabilities.